Evaluation of Traffic Flow Behaviours for Two-way Roads in Hawassa City - Manuka, Dagimwork Asele (International Journal of Scientific Research in Civil Engineering, 2019)
Recently in Ethiopia massive increase in population, way of life, car ownership and economic activities resulted rise in travel demand. Increment in travel demand are highly displayed in major city from this, city of Hawassa is good preference. Hawassa city is fast growing city and all of the above parameters are significantly observed. Due to this, the traffic flow pattern will vary time to time and corridor to corridor, so estimate and analyze this traffic flow characteristics were basic for proper traffic plan and implementation. Various combinations of motorized vehicles were stated in advancement of model and the results of the developed modal bring certain guidelines to improve the traffic flow characteristics in the urban areas under mixed traffic conditions and significantly limiting the percentage of Cars, Buses and Trucks within the range and result optimal operating speed in a given urban road facilities, for instance with 30% of (Bajaj and Trucks) and 10% of (Cars and Buses) and with 20% of Motor-cycle which is in all sub-conditions (except in third sub-condition) displays that the value for operating speeds are below 50 km hr-1 between 4m-12m lane width which are dominant combinations to be within the boundaries of facilities. Consequently, average operating speed are majorly be determined by percentage of traffic volume and then with the lane width and additional factors has impacts under mixed traffic conditions.